Diaspora, Law and Literature - Carpi, Daniela (Law & Literature, 2017)
The well-known challenges of international migration have triggered new departures in academic approaches, with 'diaspora studies' evolving as an interdisciplinary and even transdisciplinary field of study. Its emerging methodology shares concerns with another interdisciplinary field, the study of the relations between law and literature, which focuses on the ways in which the two cultural practices of law and literature mutually negotiate each other and on the question after the ontological commensurability of the domains. This volume offers, for the first time, an attempt to provide an interface between these overlapping interdisciplinary endeavours of literary studies, legal studies, and diaspora studies. In doing so, it explores new approaches and invites new perspectives on diasporas, migration and the disciplines that study them, hopefull also adding to the cultural resources of coping with a swiftly changing social landscape in a globalizing world.